Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

The Wai 262 Claim: A Claim by Māori to Indigenous Flora and Fauna - Solomon, Maui (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements; waitangi tribunal

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Chapter 11: Recovering Fagin's Ill-Gotten Gains: Settling Ngāti Kahu's Treaty of Waitangi Claims Against the Crown - Mutu, Margaret (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Orakei - Kāwharu, Hugh (Waitangi Revisited, 2005)
Keywords: government relations; hapū; history; land tenure; ngāti whatua; political action; race relations; rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Chapter 6: Rangatiratanga and Social Policy - Kawharu, Merata (Waitangi Revisited, 2005)
Keywords: crown policy; education; government relations; hauora; health; history; land tenure; race relations; rangatiratanga; social policy; tiriti o waitangi/treaty of waitangi

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal